Contemporary management of penetrating renal trauma - A national analysis. Issue 1 (January 2020) - El Hechi, Majed W.; Nederpelt, Charlie; Kongkaewpaisan, Napaporn; Bonde, Alexander; Kokoroskos, Nikolaos; Breen, Kerry; Nasser, Ahmed; Saillant, Noelle N.; Kaafarani, Haytham M.A.; Velmahos, George C.; Mendoza, April E.
Highlights: Nationwide, 18% of patients with a penetrating injury to the kidney are offered nonoperative management. With a success rate of 92%, patients are being appropriately selected for nonoperative management. Concomitant abdominal injuries & higher grade kidney injuries predict failure of nonoperative management. Abstract: Introduction: Indications for nonoperative management (NOM) after penetrating renal injury remain ill-defined. Using a national database, we sought to describe the experience of operative and nonoperative management in the United States and retrospectively examine risk factors for failure of NOM. Materials and Methods: The TQIP database 2010–2016 was used to identify patients with penetrating renal trauma. Outcomes of patients treated with an immediate operation (IO) and NOM are described. Failure of NOM was defined as the need for a renal operation after 4 h from arrival. Univariate then multivariable regression analyses were performed to identify predictors of NOM failure. Results: Out of 8139 patients with kidney trauma, 1, 842 had a penetrating mechanism of injury and were included. Of those, 89% were male, median age was 28 years, and 330 (18%) were offered NOM. Compared to IO, NOM patients were less likely to have gunshot wound (59% vs 89% p < 0.001) or high-grade renal injuries [AAST 4–5] (48% vs 76%, p < 0.001). Lower rates of in-hospital complications and shorter ICU and hospital stays were observed in the NOM group. NOM failed in 26 patients (8%). Independent predictors of NOM failure included a concomitant abdominal injury (OR = 3.99, 95% CI 1.03–23.23, p = 0.044), and every point increase in AAST grade (OR = 2.43, 95% CI 1.27–5.21, p = 0.005). Conclusions: NOM is highly successful in selected patients. Concomitant abdominal injuries and higher grade AAST injuries predict NOM failure and should be considered when selecting patients for IO or NOM.